ASSESSMENT OF THE EFFECTIVENESS OF THE INFORMATION AND DIGITAL ENVIRONMENT OF GENERAL SECONDARY EDUCATION INSTITUTIONS: THE GREAT BRITAIN EXPERIENCE - Malytska, Ірина (Journal of Information Technologies in Education (ITE), 2023)
The article is devoted to the system of assessment of the school's information and digital environment (IDE) on the example of the Great Britain experience. In order to maintain and develop a modern IDE, it is necessary to assess its state, which will help determine: the effectiveness of technology use; strengths and weaknesses of the school's digitalisation policy; further ways of its effective digitalisation. The article presents the Naace SRF (Self Review Framework) self-assessment tool, which has been created and used by Great Britain educators for over 20 years, as well as its structural elements, which were developed by various educational organisations (the Office for Standards in Education, Children's Services and Skills; education agencies; educational institutions; the Trust, etc.) The National Digital Strategies and the views of the education community were taken into account during development. Control questions are provided to help schools prepare in advance for the SRF self-assessment process. The author describes the assessment process carried out on the Naace online platform, which consists of four levels, presents general questions asked to school representatives covering the following areas: leadership and management; teaching and learning with technology; assessment of digital potential; protection of digital data; professional development; resources and technologies. The ease of use of the tool has been determined, given that the assessment data is stored in the system, so schools can independently monitor the development of digitalisation of their educational institution and formulate further digital plans. In addition, the System has developed the NaaceMark quality mark, which motivates schools to increase their level of technological development. An analysis of existing systems for assessing the effectiveness of the school's information and digital environment will help to create the own tool that will meet the requirements and needs of Ukrainian educators.